How does inflation in advanced economies affect emerging market bond yields? Empirical evidence from two channels - Sei-Wan Kim; Donghyun Park; Shu Tian (Asian Development Bank (ADB), 2023)
Increasing oil and food prices and persistent supply chain disruptions in 2022 contributed to inflation in advanced economies that had not been seen in decades. This pushed up interest rates, which in turn led to higher yields in global bond markets. This study examines two distinct channels that transmit advanced economy inflation to emerging market bond yields by employing a novel multivariable smooth transition autoregressive- vector autoregressive (STAR-VAR) model. Our empirical analysis yields two new key findings. First, advanced economy inflation has a significant effect on regime changes between expansion and contraction in emerging market bond yields. Second, the shortrun effect of advanced economy inflation on the bond yields of emerging markets is asymmetric between the expansion and contraction regimes. The effect is mostly positive in both regimes but stronger in a bond yield's contraction regime. This suggests that the response of emerging market bond yields to advanced economy inflation does not necessarily follow a simple Fisher equation relationship.
Keywords: F14; C40; C51; 330; bond yields; inflation; advanced economy; emerging market; regime change; smooth transition autoregressive model